A UWB Band-Pass Antenna with Triple-Notched Band Using Common Direction Rectangular Complementary Split-Ring Resonators - Bo Yan; Di Jiang; Ruimin Xu; Yuehang Xu (International Journal of Antennas and Propagation)
A novel ultrawideband (UWB) antenna which has a triple-band notch function is presented. The proposed antenna can block interfering signals from C-band satellite communication systems, IEEE802.11a, and HIPERLAN/2 WLAN systems for example. The antenna is excited by using novel common direction rectangular complementary split-ring resonators (CSRR) fabricated on radiating patch of the dielectric substrate with coplanar waveguide (CPW) feed strip line. The voltage standing wave ratio (VSWR) of the proposed antenna is less than 2.0 in the frequency band from 2.8 to 12 GHz, while showing a very sharp band-rejection performance at 3.9 GHz, 5.2 GHz, and 5.9 GHz. The measurement results show that the proposed antenna provides good omnidirectional field pattern over its whole frequency band excluding the rejected band, which is suitable for UWB applications.